The Quality of Fish Meal for Animal Feed and its Toxicity - ., Yuningsih (Indonesian Animal Sciences Society, 2002)
Fish meal is an important source of protein in feed. However its storage time and condition should be carefully observed as they may cause the fermentation if stored for long time. When Clostridium spp are dominant during proteolitic reactions, extensive changes to amino acids can occur by three different types of reactions: deamination, decarboxylation and coupled oxidation/ reduction, which result in the production of amines, ammonia, carbondioxide, keto acids and fatty acids. Based on the result of toxicological examination in fish meal samples which were received from 1999 to 2000 in diagnostic laboratory, Balitvet- Bogor, the samples contain ammonia: 15 samples (100%), histamine: 9 samples (64%) and nitrate: 2 samples (14%). As a conclusion histamine (decarboxilation reaction) and ammonia are a primary toxic substance in fish meal. Â Key words: Fish meal, histamine, ammonia, nitrate